Redesain Penataan Pohon Pada Rest Area Jalibar Desa Oro Oro Ombo, Kota Batu - Putri Sifaul Qolbi; Rizki Alfian; Dian Kartika Santoso (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Title: Redesign of Tree Arrangement in Jalibar Rest Area, Oro Oro Ombo Village, Batu City The Jalibar Rest Area is one of the tourist support facilities in Oro Oro Ombo Village. However, this rest area does not yet have a good green planning plan, even though one of the supporting comfort areas in the rest area is the proper arrangement of trees. This research identifies existing tree species and analyzes their functions, evaluates tree arrangements, and recommends tree arrangements based on their function and planting location. The research was conducted in the Jalibar Rest Area in Oro Oro Ombo Village, Batu District, Batu City, East Java. The analytical methods used are Key Performance Index (KPI), Comparative Study, and Spatial Mapping. Based on field observations, it is known that the Jalibar Rest Area has 123 trees with 16 types of trees. Based on the evaluation results, it is known that the suitability of the tree's function to its location, namely that the outer zone of the rest area should be planted with shade trees, guides and trees of aesthetic value. The parking zone is planted with trees that function as shade trees, guides and absorb pollutants. As well as service zones planted with trees with the functions of shade, absorbing pollutants and aesthetics. Recommendations for redesigning tree arrangements in the Jalibar Rest Area include adjusting the function of trees in each zone by maintaining appropriate tree species, replacing inappropriate tree species, adding and subtracting trees based on their planting distance.